THE POSITION OF CUSTOMARY CRIMINAL LAW IN NATIONAL CRIMINAL LAW - Zufarnesia, Zufarnesia (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
The position of customary criminal law in national criminal law can be seen in Article 5 paragraph 3 sub (b) of Law Drt No. 1/1951, Article 4 paragraph 1, Article 5 paragraph 1, Article 10 paragraph 1, and Article 50 paragraph 1 of Law No. 48/2009. Article 51 Law No.21/2001. As well as the application of the principle of formal legality and the principle of material legality. Then there is customary criminal law in the 2008 Draft Criminal Code, namely in Article 1 paragraphs 3 and 4, Article 11 paragraph 2, and Articles 67 and 12 of the 2008 Criminal Code Bill.